2021
DOI: 10.1093/burnst/tkaa047
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis and diagnosis of sepsis post burn injury

Abstract: Burn is an under-appreciated trauma that is associated with unacceptably high morbidity and mortality. Although the survival rate after devastating burn injuries has continued to increase in previous decades due to medical advances in burn wound care, nutritional and fluid resuscitation and improved infection control practices, there are still large numbers of patients at a high risk of death. One of the most common complications of burn is sepsis, which is defined as “severe organ dysfunction attributed to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 158 publications
0
60
0
8
Order By: Relevance
“… 5 Without timely and appropriate treatment, bacterial infections in burn patients may lead to sepsis, multiple organ dysfunction syndrome, or even death. 6 A survey showed that up to 75% mortality in burn patients was due to severe burns of 40% total body surface area (TBSA) or above. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 5 Without timely and appropriate treatment, bacterial infections in burn patients may lead to sepsis, multiple organ dysfunction syndrome, or even death. 6 A survey showed that up to 75% mortality in burn patients was due to severe burns of 40% total body surface area (TBSA) or above. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Wound with delayed healing more than 3 months would be referred to as chronic wound [10,228,229]. In detail, chronic wounds with impaired regenerative capacity demonstrate high levels of proinflammatory cytokines, persistent infections, and drug resistance.…”
Section: Application Of Conductive Biomaterials In Wound Healingmentioning
confidence: 99%
“…Extensive tissue damage, necrotic debris, and diseases often make wounds suffer from such issues, thus leading to prolonged inflammation and delayed proliferation and remodeling. Wound with delayed healing more than 3 months would be referred to as chronic wound [ 10 , 228 , 229 ]. In detail, chronic wounds with impaired regenerative capacity demonstrate high levels of proinflammatory cytokines, persistent infections, and drug resistance.…”
Section: Application Of Conductive Biomaterials In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Burn injury can induce multisystem stress and uncontrolled systemic inflammation, leading to mortality and morbidity [ 1 ]. Though the burn mortality rate has declined during the last 5 decades due to improved resuscitation, antibiotic therapy, surgical procedures and nutritional support [ 2 ], the mortality rate of burn patients (range 1.4–18%) remains high when compared with that of other critical care patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%